Primary and Secondary Enuresis in Children Presenting At Pediatric Outpatient Department of Combined Military Hospital Malir Cantt Karachi - Zahid, Meha; Ali, Arshad; Zaidi, Syed Taqi Hasan; Saba, Ameena; Shujaat, Wasif; Samina, Mubushra (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of primary and secondary enuresis in the children presenting at outpatient department of Tertiary Care Hospital. Study Design: A cross sectional study. Place and Duration of Study: Outpatient Department of Combined Military Hospital Malir, Karachi, from Feb to July 2019. Methodology: A total of 1200 children with age range of 5-12 years were included in the study. Children presenting with severe acute illness or those with non-willing caregivers were excluded from the study. Result: Out of the total 1200 study participants, 167 (13.9%) children gave the history of enuresis. There were 109 (65.6%) boys and 58 (34.4%) girls. The children with primary enuresis were 141 (84.3%) while 26 (15.62%) children had secondary enuresis. About 31 (18.7%) children had daytime enuresis, 115 (68.5%) had night-time and 21 (12.5%) children had both day and night time bed wetting. About 57 (34.37%) children previously got the treatment for enuresis which included fluid restriction in 21 (12.5%) and desmopressin in 36 (21.87%). Out of them 52 (91.2%) children showed complete response while 5 (8.77%) showed incomplete response. Conclusion: Our study found that enuresis is more frequent among boys. Primary enuresis is more common than secondary enuresis and nocturnal enuresis is more common than diurnal enuresis.